Landscape of phase 1 clinical trials for minors with cancer in the United States. Issue 11 (4th September 2020) - Nader, Jaclynne H.; Neel, Dylan V.; Shulman, David S.; Ma, Clement; Bourgeois, Florence; DuBois, Steven G.
Abstract: Objectives: Understanding trends in characteristics of early phase trials that allow minors with cancer to participate may inform additional efforts to improve cancer drug development for young people. Methods: We accessed data for oncology phase 1 or phase 1/2 trials in the United States from ClinicalTrials.gov with lower age bound for eligibility <18 years. Descriptive statistics were calculated and trends over time evaluated using logistic and multinomial logistic regression. Results: Six hundred twelve trials met inclusion criteria. Sixty‐five percent of trials were for older adults that also allowed minors, while 9% were exclusively for patients ≤18 years of age. Eighty‐three percent of trials included at least one novel agent, while 17% studied only conventional therapies. Fifty‐eight percent of trials studied treatments not yet Food and Drug Administration (FDA) approved (48% if exclusively for patients ≤18 years). Fifteen percent of trials for which dose‐escalation method could be determined, utilized a model‐based design. Eighteen percent of all trials were industry sponsored (48% if exclusively for patients ≤18 years). Forty‐nine percent of all trials were multicenter (69% if exclusively for patients ≤18 years). There was an increase in trials exclusively focused on patients with central nervous system (CNS) tumors over the study period ( P ≤ .02). No other temporal trends were seen. The median times from first‐in‐adult to first‐in‐pediatric for monotherapy and combination trials were 5.7 and 3.3 years, respectively. Conclusion: The paucity of clear temporal trends highlights the need for innovation in early drug development for young people. Our analysis serves as a benchmark against which to evaluate initiatives to improve pediatric cancer drug development.